Useless hearing in male Emblemasoma auditrix (Diptera, Sarcophagidae) : a case of intralocus sexual conflict during evolution of a complex sense organ? - Lakes-Harlan, Reinhard; Vries, Thomas de; Stölting, Heiko; Stumpner, Andreas; Justus Liebig University Giessen (My University, 2014)
Sensory modalities typically are important for both sexes, although sex-specific functional adaptations may occur frequently. This is true for hearing as well. Consequently, distinct behavioural functions were identified for the different insect hearing systems. Here we describe a first case, where a trait of an evolutionary novelty and a highly specialized hearing organ is adaptive in only one sex. The main function of hearing of the parasitoid fly Emblemasoma auditrix is to locate the host, males of the cicada species Okanagana rimosa, by their calling song. This task is performed by female flies, which deposit larvae into the host. We show that male E. auditrix possess a hearing sense as well. The morphology of the tympanal organ of male E. auditrix is rather similar to the female ear, which is 8% broader than the male ear. In both sexes the physiological hearing threshold is tuned to 5 kHz. Behavioural tests show that males are able to orient towards the host calling song, although phonotaxis often is incomplete. However, despite extensive observations in the field and substantial knowledge of the biology of E. auditrix, no potentially adaptive function of the male auditory sense has been identified. This unique hearing system might represent an intralocus sexual conflict, as the complex sense organ and the behavioural relevant neuronal network is adaptive for only one sex. The correlated evolution of the sense organ in both sexes might impose substantial constraints on the sensory properties of the ear. Similar constraints, although hidden, might also apply to other sensory systems in which behavioural functions differ between sexes.
Keywords: ddc:570